Analysis of the Implementation of the Livable House Priority Program in East Kalimantan Province - Harna Rizki Wisesa Wisesa; Muhammad Noor; Santi Rande; Erwin Dharmawan (Poltanesa, 2025)
This study explores the implementation of the Livable House Priority Program in East Kalimantan Province as a strategic effort to address the problem of inadequate housing and support sustainable regional development. As part of the provincial government’s commitment to achieving the Sustainable Development Goals (SDGs), especially Goal 11 Sustainable Cities and Communities the Livable House program aims to reduce the number of uninhabitable houses by providing decent, safe, and healthy housing for low-income families. The initiative integrates corporate social responsibility (CSR) through collaboration between the government and private companies operating in the region, aligning with the mandate of East Kalimantan Governor Regulation No. 27/2021. This research adopts a qualitative approach through in-depth interviews, participatory observation, focus group discussions (FGDs), and document analysis. The study focuses on three priority regions: Bontang City, Berau Regency, and Paser Regency. Findings indicate that while the program has made tangible progress in reducing uninhabitable housing and improving settlement environments, its implementation is hindered by limited corporate participation, logistical and administrative challenges, and inconsistent regional policy enforcement. The role of the private sector remains suboptimal, often due to unclear implementation guidelines, shifting political commitments, and lack of incentives. Despite these obstacles, the Livable House program has demonstrated significant potential in contributing to poverty reduction, improving social welfare, and promoting stakeholder synergy. However, to ensure long-term sustainability and scalability, the study recommends enhancing intersectoral collaboration, strengthening regulatory frameworks, fostering corporate engagement, and adopting adaptive policy models. This research contributes to public policy discourse by offering insights into the dynamics of decentralized policy implementation, highlighting the importance of collaborative governance in addressing complex social issues in developing regions.